Effects of depth of cut and feed rate on dimensional accuracy and surface roughness in CNC nesting of HMR panels - Agung Ari Purwanto; Zain Amarta; Bahtiar Rahmat; Wahyu Widiyanto; Muhammad Fahrudin (Jurnal Polimesin, 2026)
The rapid adoption of digital manufacturing and smart CNC machining in furniture production has made the optimization of machining parameters for engineered wood panels increasingly important. High Moisture Resistance (HMR) panels are widely used because of their superior moisture resistance compared with Medium Density Fiber board (MDF). However, studies on CNC machining performance of HMR panels remain limited, particularly regarding dimensional accuracy and surface roughness. This study evaluates the effects of depth of cut and feed rate in CNC nesting on dimensional accuracy and surface quality of HMR panels. Four machining combinations were tested using depths of cut of 2 and 4 mm and feed rates of 33 and 66 mm/s, with three replications for each treatment. Specimen dimensions and average surface roughness (Ra) were measured after machining. The results show that depth of cut significantly affected dimensional accuracy, while feed rate significantly influenced surface roughness. The interaction between depth of cut and feed rate was not significant for specimen length, but was significant for specimen width and roughness. Optimal dimensional accuracy and surface quality were achieved using the lowest depth of cut (2 mm) in conjunction with the lowest feed rate (33 mm/s).